Development of competency model for family physicians against the background of ‘internet plus healthcare’ in China: a mixed methods study - Ziling Ni (Human Resources for Health, 2020)
Abstract Background Identification of the service competences of family physicians is central to ensuring high-quality primary care and improving patient outcomes. However, little is known about how to assess the family physicians’ service competences in primary care settings. It is necessary to develop and validate a general model of core competences of the family physician under the stage of construction of family doctor system and implementation of ‘Internet Plus Healthcare’ service model in China. Methods The literature review, behavioural event interviews, expert consultation and questionnaire survey were performed. The scale’s 35 questions were measured by response rate, highest score, lowest score, and average score for each. Delphi method was used to assess content validity, Cronbach’s α to estimate reliability, and factor analysis to test structural validity. Respondents were randomly divided into two groups; data for one group were used for exploratory factor analysis (EFA) to explore possible model structure. Confirmatory factor analysis (CFA) was then performed. Results Effective response rate was 93.56%. Cronbach’s α coefficient of the scale was 0.977. Factor analysis showed KMO of 0.988. Bartlett’s test showed χ 2 of 22 917.515 (df = 630), p < .001. Overall authority grade of expert consultation was 0.80, and Kendall’s coefficient of concordance W was 0.194. By EFA, the five-factor model was retained after thorough consideration, and four items with factor loading less than 0.4 were proposed to obtain a five-dimension, 32-item scale. CFA was performed on the new structure, showing high goodness-of-fit test (NFI = 0.98, TLI = 0.91, SRMSR = 0.05, RMSEA = 0.04). Overall Cronbach’s α coefficients of the scale and each sub-item were greater than 0.9. Conclusions The scale has good reliability, validity, and credibility and can therefore serve as an effective tool for assessment of Chinese family physicians’ service competences.